Teaching and Learning Analytical Exposition Paragraph Writing (Dictogloss Technique) - Kholid, M. Ridho; Agustina, Rosi (Universitas Islam Negeri Raden Intan Lampung, 2017)
Writing is one of skills in English. It is often considered a difficult subject by the students. Some techniques are needed by the teacher to overcome writing difficulties. One of technique is Dictogloss. Furthermore, students often make mistake in writing while targeted to reconstruct the paragraph. The objective of the research was to describe the process of teaching and learning analytical exposition paragraph writing by using dictogloss technique and to construe the teacher’s problems and students’ problems in teaching and learning. This research was a descriptive qualitative research. The subject of the research was the eleventh grade. The researcher applied the purposive sampling technique to determine the sample. The researcher adopted and determined one class as a sample. As well, the researcher chose class XI IPA 4 for the reason that the students of this class had difficulties in mastering writing skill. The total number of the sample was 39 students. The researcher used triangulation to collect the data, they were observation, interview, and questionnaire. From the data analysis, the researcher found the teacher who got some difficulties to handle the crowded class. Besides that, the teacher had low voice in teaching so the students did not hear clearly until behind of the class. Second, the students’ –in learning analytical exposition paragraph writing by using dictogloss– had adversities in reconstructing the version of analytical exposition paragraph. That was because they had limited vocabulary, poor organization, spelling, and capitalization letters. A step form that, the students had lack motivation in learning writing.